Comparison of the Added Value of Contrast-Enhanced 3D Fluid-Attenuated Inversion Recovery and Magnetization-Prepared Rapid Acquisition of Gradient Echo Sequences in Relation to Conventional Postcontrast T1-Weighted Images for the Evaluation of Leptomeningeal Diseases at 3T - Fukuoka, H.; Hirai, T.; Okuda, T.; Shigematsu, Y.; Sasao, A.; Kimura, E.; Hirano, T.; Yano, S.; Murakami, R.; Yamashita, Y. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: The usefulness of contrast-enhanced 3D T2-FLAIR MR imaging for the evaluation of leptomeningeal diseases has not been systematically investigated. The purpose of this study was to assess the value added by contrast-enhanced 3D T2-FLAIR and MPRAGE sequences to conventional postcontrast T1-weighted images in the evaluation of leptomeningeal diseases. We also undertook in vitro studies in attempts to understand the consequences of our patient study. MATERIALS AND METHODS: Twelve patients with confirmed leptomeningeal diseases underwent postcontrast T1-weighted, MPRAGE, and 3D T2-FLAIR imaging at 3T. Two radiologists independently assessed the presence of additional information on postcontrast 3D MR images compared with postcontrast T1-weighted images. The effect of different Gd concentrations and flow velocities on the signal intensity on 3D T2-FLAIR images was investigated in vitro. RESULTS: According to both reviewers, 3D T2-FLAIR images yielded significantly more information than did MPRAGE images (P < .05 and P < .01, respectively). In the in vitro study, 3D T2-FLAIR was more highly sensitive to low Gd concentrations and less sensitive to high Gd concentrations than were T1-weighted or MPRAGE sequences. On 3D T2-FLAIR sequences, at a flow velocity exceeding 1.0 cm/s, the signal intensity of blood-mimicking fluids at concentrations of 0 and 0.1 mmol/L was as low as at 1.3 mmol/L. CONCLUSIONS: For the depiction of leptomeningeal diseases, postcontrast 3D T2-FLAIR provides more additional information than postcontrast MPRAGE imaging. The superiority of the 3D T2-FLAIR sequence is associated with its high sensitivity to flow. FLAIRfluid-attenuated inversion recoveryGdgadoliniumMPRAGEmagnetization-prepared rapid acquisition of gradient echoSIsignal intensity